Emotion regulation and decision-making in persons with dementia: A scoping review. (July 2021) - Perach, Rotem; Rusted, Jennifer; Harris, Peter R.; Miles, Eleanor; ,
Background and Objectives: Emotion is integral to decision-making, and emotion regulation is associated with improved well-being in older age. Persons with dementia are likely to experience impairments in emotion regulation processes that can potentially contribute to differential decision-making and well-being outcomes. To promote the development of theoretical models of well-being in dementia, we review the quantitative evidence concerning the associations between emotion regulation and decision-making in dementia. Methods: Scoping review. Results: Seven studies of persons with dementia met our criteria. In persons with frontotemporal lobar degeneration, emotion regulation processes that precede the emotional experience were associated with decision-making in a moral (but not uncertainty) context. Independent of type of dementia, evidence concerning the associations between emotion regulation processes that occur after emotion is experienced and decision-making was mixed and drew on different methodologies. No studies relating to the associations between decision-making in dementia and several emotion regulation processes and strategies were found. Conclusions: In this review, we sought to clarify the concept of everyday decision-making in dementia and map the current state of evidence concerning its associations with emotion regulation. Our findings show that emotion regulation processes are associated with decision-making in dementia, depending on type of decision-making assessment and emotional experience. We outline the gaps in the literature to set a research agenda for promoting our understanding of how emotion regulation processes can shape the various decisions that are made by persons with dementia on a daily basis.